(untitled) (Research, Society and Development, 2022)
Changes in nutritional status are directly related to excessive consumption of foods, especially processed and ultra-processed foods. That’s because these food sources are rich in sodium, sugar and fats, as well as food additives. In childhood, the risk of developing nutritional deficiencies is high due to the increase in nutritional needs, at this stage commensality is also important since there is the formation of eating habits. The objective of the research is to understand how food impacts the nutritional status of children in a school in the federal district, through a descriptive and cross-sectional case study. The work was carried out with children who attend a school in brasília, in the morning, the sample was defined by convenience. The first stage was carried out by a questionnaire evaluating life and eating habits and in the second stage the critical points were defined, which resulted in a regular consumption of fresh foods, such as fruits (65.6%), vegetables and legumes (59.4%) and minimally processed foods, such as rice and beans (46.9%), but with a high consumption of ultra-processed foods, especially sugary drinks (50%), sweets and candies (43.8%). In addition, the lack of commensality in the realization of meals prevails in most children. However, the majority of the public had an adequate weight (76.6%), height (93.3%) and bmi (56.6%) for their age. Concluding that there is a need for periodic and continuous nutritional monitoring with evaluation of the dietary pattern inside and outside the school of the evaluated public.